Genomic regions and enrichment analyses associated with carcass composition indicator traits in Nellore cattle - Silva, Rosiane P.; Berton, Mariana P. [UNESP]; Grigoletto, Laís; Carvalho, Felipe E.; Silva, Rafael M. O.; Peripolli, Elisa [UNESP]; Castro, Letícia M.; Ferraz, José Bento S.; Eler, Joanir P.; Lôbo, Raysildo B.; Baldi, Fernando (Wiley, 2019)
The aim of this study was to estimate genetic parameters and identify genomic regions associated with carcass traits obtained by ultrasound and visual scores in Nellore cattle. Data from ~66,000 animals from the National Association of Breeders and Researchers (ANCP) were used. The variance components for backfat thickness, rump fat thickness and Longissimus muscle area (LMA) were estimated considering a linear model whereas a threshold model for body structure (BS), finishing precocity (FP) and musculature (MS) traits. The SNP solutions were estimated using the ssGBLUP approach by considering windows of 10 consecutive SNPs. Regions that accounted for more than 1.0% of the additive genetic variance were used. Genes identified within the significant windows, such as FOXA3, AP2S1, FKRP, NPASI and ATP6V1G1, were found to be related with MS, while OMA1 and FFGY with BS and FP traits. The PLTP, TNNC2 and GPAT2 genes were found in the regions associated with LMA, as well as TKT, FNDC5 and CHRND can strongly be related with fat deposition. Gene enrichment analysis revealed processes that might be directly influenced the organism growth and development. These results should help to better understand the genetic and physiological mechanisms regulating growth and body composition, muscle tissue development and subcutaneous fat expression, and this information might be useful for future genomic studies in Nellore cattle.
Keywords: beef cattle; Bos taurus indicus; GWAS; ultrasonography measurement; visual score traits